ANALISIS FUNGSI PERENCANAAN DAN PENGAWASAN TERHADAP PROSES PRODUKSI PADA CV. PERMATA - Debby Marthalia (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
The raw material is the most important factor or can be regarded as a major element in a production process but without the supply of raw materials and monitors, a good planning will be the bottleneck in the production process. Problems of planning and supervision to determine the investment in inventories of raw materials is an important issue in any company because it has a direct effect on the company’s material. The production process in the company can not run optimally. Ordering supplies and raw materials should be adjusted to the magnitude of the needs. Calculation Economic Order Quantity is expected to finish due to the excess and shortage of raw materials, so that the company can make the production process optimally. The results showed that the planning and supervision greatly affect the production process at CV. Permata. Total purchases of invitation papers were decline leads to a lack of raw material inventory in the warehouse and the lack of planning and supervision of the production process and raw materials, so that in the event of sudden demand, unexpected consumer company could not meet the demand. The results of the analysis of the correlation method with causal and time series methods seen that the production and sales amount in 2009 decreased, which affected the company's revenue.